1998
DOI: 10.1093/ps/77.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Lysine: Amino acid requirements of broiler breeders

Abstract: Because feed intake is controlled in broiler breeders, amino acid supply is determined by the composition of the feed and the level of feed intake. Controlling amino acid supply during the laying cycle can be facilitated by the use of a model for calculating requirements. A possible model is outlined and the various components discussed. Typical calculations suggest that the model can provide a useful basis for practical feeding decisions. Model elements include: levels of animal performance; utilization of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 20 publications
1
21
1
1
Order By: Relevance
“…Based on the values of methionine content of whole egg (3.646 mg/g egg) (Lunven et al 1973) and the efficiency of dietary methionine for egg production (55.2%) (Nonis & Gous 2006), the methionine requirement for producing eggs is up to 661 mg/100 g egg, so the egg mass has critical effect on the methionine requirement of broiler breeders. The methionine required for maintenance was also estimated as suggested by Nonis and Gous (2006) and Fisher (1998) to be 115.6 mg/hen/day. In the present study, the egg mass ranged from 27-30 g/hen/day, so the total methionine requirement of broiler breeders was estimated to be 291.1-313.9 mg/hen/day, which was just slightly higher than the amount supplied by the basal diet (262.5-273 mg/hen/day).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the values of methionine content of whole egg (3.646 mg/g egg) (Lunven et al 1973) and the efficiency of dietary methionine for egg production (55.2%) (Nonis & Gous 2006), the methionine requirement for producing eggs is up to 661 mg/100 g egg, so the egg mass has critical effect on the methionine requirement of broiler breeders. The methionine required for maintenance was also estimated as suggested by Nonis and Gous (2006) and Fisher (1998) to be 115.6 mg/hen/day. In the present study, the egg mass ranged from 27-30 g/hen/day, so the total methionine requirement of broiler breeders was estimated to be 291.1-313.9 mg/hen/day, which was just slightly higher than the amount supplied by the basal diet (262.5-273 mg/hen/day).…”
Section: Discussionmentioning
confidence: 99%
“…Initially this was on economic grounds but their use is now being encouraged by concerns over N-pollution (Fisher, 2000). When modelling the amino acid requirements of broiler breeder hens, a question that requires closer scrutiny is the efficiency with which synthetic amino acids are used for egg production.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicated that quadratic-plateau model resulted in Fisher (1998) suggested that lysine intake requirement for maximum egg production from 27 to 33 week of age might be 893 mg based on the 'Reading model'. NRC (1994) recommendations for daily lysine intake in meat-type breeder hens was 765 mg. Harms and Ivey (1992) proposed the total lysine requirement to maximize egg production at 824 mg with a daily protein intake of 18.55 g. Harms and Russell (1995) reported total lysine requirement of 845 mg for maximum egg production, egg mass and egg content when daily intake of 18.07 g protein was provided.…”
Section: Resultsmentioning
confidence: 76%
“…These differences between previous (Harms and Ivey, 1992; Harms and Russell, 1995;Fisher, 1998) and recent studies of lysine requirement could be partially explained improvement of genetic potential in broiler breeders would necessarily require more nutrients (Hayes et al, 2013). The strains with greater growth rate should have higher nutrients needs for their muscle development .…”
Section: Resultsmentioning
confidence: 91%